Formation of a comprehensive program of marketing strategy measures for an industrial company in a changing competitive environment - O.A. Temchenko; V.M. Radko; D.Ya. Madzharova (Економіка, управління та адміністрування)
The formation of a comprehensive program of marketing strategy measures for an industrial company in a changing competitive environment is a key task to ensure its stability and adaptation to market changes. A proposed model includes three main stages: analysis of the market environment, development of targeted measures (pricing, communication and product strategies) and their implementation with subsequent monitoring of effectiveness. The assessment methodology involves determining the priority of measures and their alignment with the company’s strategic goals. The use of innovative marketing tools, such as CRM systems and analytical platforms, allows for a more effective response to market challenges. To evaluate the effectiveness of the marketing program, a methodology is proposed that includes quantitative and qualitative indicators, as well as the prioritization of each measure in accordance with the company’s strategic objectives. Developing an effective marketing strategy is critically important for industrial companies operating inconstantly changing market conditions. The strategy should not only ensure adaptation to current conditions but also provide resilience against potential crisis situations. The proposed approach to marketing strategy formation can be used by large industrial companies to enhance their competitiveness. The formation of a comprehensive program of marketing measures is a key element of the successful functioning of industrial companies, as it contributes not only to improving competitiveness but also to minimizing the impact of crisis situations on the company’s future activities. PEST-analysis is used to assess external factors that influence the company’s market environment, including political, economic, social and technological aspects. SWOT-matrix helps identify the company’s strengths and weaknesses, as well as opportunities and threats, allowing for a more precise strategic planning process.